Emerging providers' international co-operation for development - Benn, Julia (OECD Development Co-operation Working Papers, 2017)
This paper shows that development co-operation from emerging providers - i.e. countries beyond the OECD Development Assistance Committee (DAC) - significantly increased in recent years, reaching 17% of total global development co-operation in 2014. It also presents a rough estimate, of USD 300 billion, of broader international co-operation by emerging providers and it sets out what types of instruments are used to provide this broader international co-operation. Very little is known about broader international co-operation by emerging providers and the scarce information that is available on different countries cannot be compared. This paper concludes that more information on, and a global measure of, international co-operation for development are needed to enable developing countries to manage the external support they receive and to enable further analysis of the increasingly important role that emerging providers play in developing countries